A novel quantum field approach to photoexcited insulators - Klotins, E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
In order to predict optical properties of insulating materials under intensive laser excitation, we generalized methods of quantum electrodynamics, allowing us to simulate excitation of electrons and holes, interacting with each other and acoustic phonons. The prototypical model considers a two-band dielectric material characterized by the dispersion relations for electron and hole states. We developed a universal description of excited electrons, holes and acoustic phonons within joint quantum kinetics formalism. Illustrative solutions for the quasiparticle birth-annihilation operators, applicable at short laser pulses at 0 K, are obtained by the transition from the macroscopic description to the quantum field formalism.